Enhancing Oral Bioavailability of Apigenin Using a Bioactive Self-Nanoemulsifying Drug Delivery System (Bio-SNEDDS): In Vitro, In Vivo and Stability Evaluations - Mohsin Kazi; Abdullah Alhajri; Sultan M. Alshehri; Ehab M. Elzayat; Osaid T. Al Meanazel; Faiyaz Shakeel; Omar Noman; Mohammad A. Altamimi; Fars K. Alanazi (Pharmaceutics, 2020)
Apigenin (APG) is a very well-known flavonoid for its anti-inflammatory and anticancer properties. The purpose of this study is to improve the solubility and bioavailability of APG using a stable bioactive self-nanoemulsifying drug delivery system (Bio-SNEDDS). APG was incorporated in an oil phase comprising coconut oil fatty acid, Imwitor 988, Transcutol P, and HCO30 to form a Bio-SNEDDS. This preparation was characterized for morphology, particle size, and transmission electron microscopy (TEM). The APG performance was investigated in terms of loading, precipitation, release and stability tests from the optimal Bio-SNEDDS. An antimicrobial test was performed to investigate the activity of the Bio-SNEDDS against the selected strains. Bioavailability of the Bio-SNEDDS was evaluated using Wister rats against the commercial oral product and the pure drug. The results demonstrated the formation of an efficient nanosized (57 nm) Bio-SNEDDS with a drug loading of 12.50 mg/gm which is around 500-fold higher than free APG. TEM analysis revealed the formation of spherical and homogeneous nanodroplets of less than 60 nm. The dissolution rate was faster than the commercial product and was able to maintain 90% APG in gastro intestinal solution for more than 4 h. A stability study demonstrated that the Bio-SNEDDS is stable at a harsh condition. The in vivo pharmacokinetics parameters of the Bio-SNEDDS formulation in comparison to the pure drug showed a significant increase in maximum concentration (Cmax) and area under the curve (AUC (0–t)) of 105.05% and 91.32%, respectively. Moreover, the antimicrobial study revealed moderate inhibition in the bacterial growth rate. The APG-Bio-SNEDDS could serve as potential carrier aimed at improving the clinical application of APG.